PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI ADMINISTRASI PADA TOKO JAMUR MAS - Yosep -; Alexander Setiawan; Silvia Rostianingsih (Jurnal Infra, 2013)
Jamur Mas is a store which sell and buy goods of daily needs. This store has some problems, which are counting of profit and loss, inventory and account receivable and account payable list. Problems that occur are in the recording, where all the recording is still done manually, this recording has a big risk.To answer these problems, then made an application, this application is developed and made with Microsoft Visual Studio 2005.Net and Microsoft SQL Server 2005 as a data storage. This application has some features which are buying and selling process, inventory and financial statement. This financial statement is including account payable statement, inventory statement, selling statement, buying statement, also profit and loss statement.Conclusion of this application, and from the results of the testing system can develop Jamur Mas Stores’s business as well, and then that can be making it easier for owners to conduct checks on the transactions that occurred and the stock of goods.